FORMULATION AND EVALUATION OF NILAVEMBU KUDINEERCAPSULES - M, Ramanathan; L, Subramanian; T, Poongodi; S, Manish; E, Muneeswari; P, Pavithra; S, Pugalendran (Asian Journal of Pharmaceutical Research and Development, 2019)
The herbal medicine Nilavembu Kudineer is very effective in viral fevers. The study was effort to prepare a Nilavembu Kudineerherbal capsule from Nilavembu Kudineer churnam. The task of this work is, to detainment of active biomolecules and ensure their biological activity. The Nilavembu Kudineerchurnamwas extracted by ethanol and water solvents, then the extract was dried. The resultant dried extract powder was screened by various chemical and microbiological tests for to ensure the potency. The results confirms that both the extract haveactive biomolecules and possess their activity. Based on the microbiological activity NVK water extract was comparatively better than the ethanol using extract powder. The dried NVK water extract powder capsules complies with standards of capsule pre and post filling parameters such as angle of repose, bulk density, tapped density, carr’s index and hausner’s ratio. The filled NVK capsule complies the post filling evaluations of weight variation, disintegration. In future stability, dosage titrations and more number of microbial test need to conduct for their effectiveness of the formulation.